The Girl Is Mine: Reframing Intimate Partner Violence and Sex Work as Intersectional Spaces of Gender-Based Violence - Thaller, Jonel; Cimino, Andrea N. (Violence against women, 2017)
Intimate partner violence (IPV) and sex work have been primarily constructed as mutually exclusive phenomena within scholarly literature, though both can be situated under the umbrella of gender-based violence and traced to male sexual proprietariness. Specialized research has resulted in deeper understanding of nuanced categorizations of sub-phenomena within both IPV and sex work, with parallel constructions along a spectrum of increasing danger. However, the scholarly construction of these continua as parallel—and thus unrelated—disguises the systemic nature of each form of violence and potentially pits victims against each other in the struggle for legitimacy. We propose a more systemic approach to understanding and researching IPV and sex work and provide examples of research already moving in this direction.